Rekonstruksi Epistemologis dan Genealogi Pemikiran Ekonomi Syariah di Kerajaan Islam Nusantara: Analisis Manuskrip, Institusi Ekonomi, Kebijakan Fiskal, dan Perdagangan dalam Evolusi Peradaban Ekonomi Islam Pramodern - Muhammad Widinur Caronge; S. Muhammad Nurcholis Assagaf; Idris Parakkasi; Siradjuddin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Departing from the limited number of studies that position Islamic economics as a contextual historical product. This research aims to reconstruct the epistemology and trace the genealogy of Islamic economic thought in the pre-modern Islamic kingdoms of the Nusantara by highlighting the role of manuscripts, economic institutions, fiscal policies, and trade practices in shaping the early Islamic economic system of Indonesia. This study employs a qualitative approach using historical discourse analysis, philological examination of Malay Arabic manuscripts, and genealogical mapping of ideas. The findings reveal that the epistemology of Islamic economics in the Nusantara represents a hybrid construction integrating Islamic principles sharia, local customs ‘urf, and maritime trade networks. Institutions such as the baitulmal, hisbah, and syahbandar played crucial roles in establishing equitable fiscal systems and market supervision. The intellectual genealogy demonstrates continuity between royal scholars’ fatwas, state economic policies, and coastal community practices, which later became the conceptual foundation for the development of modern Islamic economics in Indonesia. This study underscores the importance of interpreting Islamic economics through historical, contextual, and epistemological perspectives to uncover its intellectual roots within the Nusantara tradition.